Histopathological effect of the insecticidal principle from psychic nut, Jatropha curcas Linn. on cotton bollworm Helicoverpa armigera (Hubn.) (1992)
The mechanism of the insecticidal action of the crude oils from Jatropha curcas seed kernels or leaves on Helicoverpa armigera (Hubn.) (cotton bollworm) was determined at the physiological level. The H. armigera larva reared on J. curcas oil-treated diet or its pupa had few hemocytes. The epidermal cells were cuboidal and disarranged instead of being columnar and intact as in the normal insects. The larval-pupal intermediates occurred as a consequence of some abnormal histological processes such as epidermal tissue breakdown, reduction in hemocyte count and extensive fat body vacuolation. The ovarioles of females that emerged from treated larvae showed malformations in the oocytes while the males had few spermatozoa. Based on histopathological effect on H. armigera, the crude J. curcas oils were active as JH mimics.
Keywords: Entomology